Presence of Salmonella sp. In Tilapia and Catfish from Cages in Pahandut Seberang Along the Kahayan River Flow - Kurniawan, Mutiara; Praja, Rian Ka; Widiarti, Astri; Hanasia, Hanasia; Toemon, Angeline Novia (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Salmonellosis is a zoonosis, which means that it may be spread from animals to people through fish meat. It is a sickness brought on by an infection with the salmonella bacteria that infect humans and animals and invade the digestive tract. According to data from the Institute for Health Metrics and Evaluation, the global rate of salmonellosis in 2019 was 4.22 cases per 100,000 people, with a 1.72 fatality rate. Indonesia had a mortality rate of 2.42 and 5.82 per 100,000 people 2019. The objective of this study is to identify Salmonella sp. bacteria in 14 samples of river water, catfish (Clariidae), and tilapia (Oreochromis niloticus) raised in rivers. This study includes two water samples, three catfish samples, and nine tilapia samples from the cage of the Pahandut Seberang River in Palangka Raya City. It employs a descriptive research design using an experimental technique. Among the metrics noted is the detection of Salmonella sp. The study found that all water samples, tilapia, and catfish tested positive for Salmonella sp bacteria in the selective media Salmonella Shigella Agar (SSA), that 14 samples (100%) in the gram staining test displayed the traits of Salmonella sp bacteria, and that 5 samples (B N1, C N2-3 samples in tilapia, B L1 samples in catfish, and water sample 2 showed the type of Salmonella paratyphoid b bacteria) and 9 samples, namely samples Salmonella tyhpimarium bacteria were found in samples A L1, C L1 in catfish, B N2-3, C N1 in tilapia, and water 1. As a result, every sample surpassed the SNI 7388:2009 maximum level of microbial contamination, which is positive/25g. According to the Indonesian National Standardization Agency's SNI 7388:2009 guidelines for the upper limit of microbial contamination in food, the tilapia meat, catfish, and river water in the river cage of Kahayan Pahandut Seberang Palangka Raya City do not satisfy the requirements.